MUSLIM CONSUMER’S INCLINATIONS TOWARDS NON-CERTIFIED HALAL FOOD OUTLETS - Syazwani Ya,; Ahmad Nizan Mat Noor,; Abdul Hakim Asmadi,; Ismalaili Ismail,; Nik Azlina Nik Abdullah,; Ima Ilyani Ibrahim,; Nurul Farihin Mhd Nasir, (Journal of Islamic, Social, Economics and Development, 2023)
Recently, many food outlets in Malaysia without non-certified Halal was mushrooming such as Japanese and Korean restaurants. Surprisingly, it indicates positive vibes among Malaysian and Muslims predominantly. Consequently, the purpose of this research was to identify the factors, specifically ‘food quality’ and ‘service quality’ that influence Muslim consumer’s inclinations towards non-certified Halal food outlets. In this study, the population was utilizing all Muslim consumers that lives around Malaysia. A self-administered questionnaires were distributed via online and the respondents were chosen by using judgmental sampling technique. The findings had revealed that the entire formulated hypotheses were proven to have a positive and significant influence. Thus, it was indicated that Muslim consumers are concern about the importance of food quality and service quality even though they spend money on non-certified Halal food outlets. The findings of the study should assist food operators to enhance the level of food quality and their services towards customer.